The Role of BAZNAS in Empowering Communities Affected by the Recession through the Mustahik Economic Empowerment Institute - Muhammad Khoiru Sa'i; Muh. Nashirudin; Rial Fuadi (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this essay is to provide a deeper knowledge of the function of BAZNAS through Mustahik Economic Empowerment Institute and funds for Zakat, Infak, and Sedelah (ZIS) were distributed during the recession. This research is library research, i.e., research conducted in libraries utilizing library research data collection techniques derived from secondary data, i.e., data gathered indirectly by researchers (research object), however from a different source, such as books, websites, audit financial reports for 2020 and 2021, target achievement pillars of collection in the BAZNAS RI Strategic Plan (Renstra) for 2020-2025, Central Bureau of Statistics (BPS) data for 2020 and 2021, journals, documents, regulations related to objects research. The distribution of zakat funding through the Mustahik Economic Empowerment Institute (LPEM), which played a critical role in empowering communities affected by the recession due to the Covid-19 pandemic, is carried out in both rural and urban areas. The distribution and distribution of Zakat, Infaq, and Alms (ZIS) funds conducted by BAZNAS in 2020 and 2021 have been granted to mustahik, particularly the poor who are truly afflicted by the recession, and in compliance with applicable legislation. Infaq and alms funds declined as a result of the worsening Indonesian economy, whereas zakat funds received by BAZNAS in 2020 and 2021 grew.